Kearifan Lokal pada Perwujudan Tathagata di Candi Borobudur - Gaya Mentari (Titian: Jurnal Ilmu Humaniora, 2021)
This study describes about the form of local genius from tathagata Statue in Borobudur temple. Tathagata is a term to call someone who reach the truth of life. This Tathagata becomes the Buddha image which has certain characteristic (like hand gesture or mudra, and sit gesture). This study using 20 Tathagata in Rupadhatu terrace of Borobudur. Five characteristic of local genious which told by Ayatrohaedi (1986) become reference for showing the local genious that exist in Tathagata statue in Borobudur temple. The purpose of this article is giving new opinion that since Hindu-Buddha period, the old Javanesche artist (silpin) had been able to integrate foreign culture within local culture in the art and placement form of tathagata image. The research found that Tathagata have unique charateristic in art style and the placement which are the form of local genious from the Javanesche artist.